2011
DOI: 10.1128/aac.01123-10
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Phage Therapy in Treating Klebsiella pneumoniae -Mediated Liver Abscesses and Bacteremia in Mice

Abstract: Intragastric inoculation of mice with Klebsiella pneumoniae can cause liver abscesses, necrosis of liver tissues, and bacteremia. A newly isolated phage (NK5) with lytic activity for K. pneumoniae was used to treat K. pneumoniae infection in an intragastric model. Both intraperitoneal and intragastric administration of a single dose of NK5 lower than 2 ؋ 10 8 PFU at 30 min after K. pneumoniae infection was able to protect mice from death in a dose-dependent manner, but the efficacy achieved with a low dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
97
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 44 publications
8
97
1
3
Order By: Relevance
“…This confirms earlier data from experiments in mice 61 and in broilers in which dietary supplementation with phages increased liver weight 62.…”
Section: Safety Of Phage Therapysupporting
confidence: 91%
“…This confirms earlier data from experiments in mice 61 and in broilers in which dietary supplementation with phages increased liver weight 62.…”
Section: Safety Of Phage Therapysupporting
confidence: 91%
“…Patterns of those cytokine differences were not dose related, indicating that phage treatment did not result in a strong immune response [42] (for normal ranges, see [43]). Tothova et al confirmed that phage therapy of urinary tract infections in mice attenuates the expression of proinflammatory cytokines [44], and the same effect was reported by Hung et al using a model of Klebsiella pneumoniae mediated liver abscess and bacteremia in mice [45]. In mice fed with murine norovirus, the inflammatory cytokine profiling showed increased levels of IL-1α, IL-1β, IL-2, IL-10, IL-12, IFN-γ and IFN-α.…”
Section: • Phages and Inflammationsupporting
confidence: 60%
“…Though used for decades in Eastern Europe, successful phage therapy has been demonstrated only recently in experimental models (8,11,15,27,36,40,43,44). Because bacteriophage replicate at infection sites, efficacy may require just a single dose (23,40). Although phage-resistant mutants may be selected during treatment, they are often less virulent (8,23) and thus do not usually compromise treatment.…”
mentioning
confidence: 99%
“…Because bacteriophage replicate at infection sites, efficacy may require just a single dose (23,40). Although phage-resistant mutants may be selected during treatment, they are often less virulent (8,23) and thus do not usually compromise treatment. In general, the specificity of phage infection ensures that the bulk of the body's microflora is unaffected (6,12).…”
mentioning
confidence: 99%